(untitled) (Medico Legal Update, 2020)
Assessment of serum ferritin, FSH, LH, estradiol, testosterone levels in ?-thalassemia major patients. A total 50 (30 male and 20 female) children with ?- thalassemia major patients with ages range 11- 16 years and 50 age and sex matched healthy adolescents as control group were included in this study. The study subjects divided into 2 more subgroups: 11-13 years, and 14-16 years to measure mean serum ferritin, FSH, LH, testosterone, estradiol hormones. There was significant increase (P <0.05) in serum ferritin level in male and female patients as compared to control groups. Male patients have significant decreased (P<0.05)serum levels of FSH, LH, testosterone and estradiol, while female patients have non-significant (P >0.05) high serum FSH and testosterone levels, but LH, estradiol levels were non-significant (P>0.05) lowas compared to control. In age subgroup 11–13 years, male patients have significant (P<0.05) decreased reproductive hormones levels as compared to control, however in 14 – 16 years subgroups serum FSH,LH and estradiol levels in male patients were significantly decreased as compared to control (P<0.05), whereas,hormones levels in female patients didn’t show significant differences in comparison to female control in both age subgroups (P>0.05). Serum ferritin had an inverse correlation with serum FSH, LH, testosterone, estradiol hormones levels. Patients with ?- thalassemia major have iron overload with inverse correlation between gonadal hormones and serum ferritin.